Pensions at a Glance : Latin America and the Caribbean - OECD (Paris: OECD Publishing, 2015)
The biggest pension policy challenge faced by most countries in Latin America and the Caribbean (LAC) today is low coverage of formal pension systems, both in terms of the proportion of workers participating in pension schemes and the proportion of the elderly receiving some kind of pension income. Efforts to close the coverage gap, for example, through non-contributory pensions, are therefore at the heart of the pension policy debate in the region. However, these policies might pose significant fiscal challenges in the next decades as the population ages. Chapter 2 presents three main indicators describing the demographic conditions relevant for pension policy, namely fertility rates, life expectancy and old-age support ratios. This is followed by a systematic comparison, in Chapter 3, of system designs across countries using the standard OECD Pensions at a Glance typology and presenting several key indicators of adequacy, including gender-specific gross and net replacement rates and pension wealth at different income levels. Finally, Chapter 4 provides the profiles of each pension system in Latin America and the Caribbean in terms of their architecture, rules and parameters.